How does entry regulation influence entry into self-employment and occupational mobility? - Susanne Prantl; Alexandra Spitz-Oener (Institute for the Study of Labor (IZA), 2009)
We analyze how an entry regulation that imposes a mandatory educational standard affects entry into self-employment and occupational mobility. We exploit the German reunification as a natural experiment and identify regulatory effects by comparing differences between regulated occupations and unregulated occupations in East Germany to the corresponding differences in West Germany after reunification. Consistent with our expectations, we find that entry regulation reduces entry into self-employment and occupational mobility after reunification more in regulated occupations in East Germany than in West Germany. Our findings are relevant for transition or emerging economies as well as for mature market economies requiring large structural changes after unforeseen economic shocks.
Keywords: J24; J62; K20; L11; L51; M13; 330; Entry regulation; self-employment; occupational mobility; Berufswahl; Selbstständige; Arbeitsmobilität; Berufsrecht; Regulierung; Neue Bundesländer; Alte Bundesländer; Deutschland